Оптимізація електрохімічного синтезу нітроген (II) оксиду - Сахненко, Микола Дмитрович; Кравченко, А. В. (НТУ "ХПІ", 2006)
Обґрунтовано термодинамічні передумови електрохімічного способу одержання стабільних мікропотоків оксиду азоту (II).

The thermodynamic aspects of electrochemical method for Nitrogen(II) oxide steady micro flow were observed. The partial reactions kinetic parameters and limiting stages are established. The NO+ reduction from concentrated sulphuric acid solutions was shown to be accompanied by preceding chemical stage and adsorption of electrode-active particles. The technological parameters were optimized in terms of the high efficiency of nitrogen (II) oxide synthesis
Keywords: сенсорні пристрої; селективна чутливість; газочутливі матеріали; фундаментальні властивості; газові середовища; стабільні мікропотоки